Estudos de acoplamento spin-órbita em dinâmica do sistema solar - Boldrin, Luiz Augusto Guimarães [UNESP] (2015)
We conducted two different studies about the spin-orbit coupling. One of them was about the origin of Uranus obliquity, that still remains unknown. Some theories of formations have been published in the last decades, the two most cited is: by collision (Uranus suffered a great tangential collision) and by a resonance between Uranus rotation and a satellite. We focused our study on the resonance model. Based on article of Boué & Laskar (2010), in which the authors study the origin of Uranus obliquity by a resonance that occurs only in the presence of a large satellite (Satellite X). We did a numerical study of this problem. Using orbits previously integrated by Nice Model, we studied the possibility of obtaining the current Uranus obliquity due to disturbances of the giant planets, the Sun and the Satellite X. Our results show that the Satellite X causes growth in Uranus obliquity and so may be the responsible for the current configuration of the Uranus rotation axis. And this growth of obliquity occurs only for certain configurations of semi-major axis and mass of the Satellite X, and maximum when the resonant angle ( _) (Uranus's equator longitude less the longitude of the ascending node of the Satellite X) is zero and minimal when it is 180 degrees. However, as in the previous study, it was only possible to reproduce the current Uranus obliquity with Satellite X with excessively large masses, about 0:01 mass of Uranus. The simulations also showed that Satellite X causes instability in the satellite with internal orbits until extinguishing them. Another study was about the origin of binary asteroid systems through rotational fission. The process of rotational fission of asteroids has been studied theoretically Scheeres (2007) and numerically Jacobson & Scheeres (2011) with simplified models restricted to planar motion. However, the observed physical configuration of contact ... (Complete abstract click electronic access below)